1993
DOI: 10.1159/000133587
|View full text |Cite
|
Sign up to set email alerts
|

Genome distribution, chromosomal allocation, and organization of the major and minor satellite DNAs in 11 species and subspecies of the genus Mus

Abstract: We compared the genome distribution, chromosomal allocation, and organization of the major and minor satellite DNAs (satDNAs) in 11 species and subspecies of the genus Mus. Southern blot analysis of the major and minor satDNAs showed similar fragment profiles in all 11 species, with the exception of M. cervicolor and M. cookii for the major satDNAs and M. caroli, M. cervicolor, and M. cookii for the minor satDNAs, where these sequences could not be detected by the probes used. In situ hybridization of the majo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0
8

Year Published

1994
1994
2015
2015

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 7 publications
3
32
0
8
Order By: Relevance
“…Data we have recently obtained in Mus domesticus by banding after restriction enzyme digestion (Garagna et al, 1992), Southern blot analysis and the energy transfer test (Garagna et al, 1993) demonstrate a very peculiar location and structure of the satellite DNA sequence in long tandem repeat sequences that fit our proposed model very well, because homologous sequences appear to be sequentially reiterated so as to increase the probability of DNA-DNA hybridization between centromeres of different chromosomes.…”
Section: An Alloperipatric Model Of Chromosome Speciationsupporting
confidence: 59%
“…Data we have recently obtained in Mus domesticus by banding after restriction enzyme digestion (Garagna et al, 1992), Southern blot analysis and the energy transfer test (Garagna et al, 1993) demonstrate a very peculiar location and structure of the satellite DNA sequence in long tandem repeat sequences that fit our proposed model very well, because homologous sequences appear to be sequentially reiterated so as to increase the probability of DNA-DNA hybridization between centromeres of different chromosomes.…”
Section: An Alloperipatric Model Of Chromosome Speciationsupporting
confidence: 59%
“…Previous studies have shown that minor satellite is present in varying amounts on Rob chromosomes. This suggests that different exchange sites within the minor satellite array and͞or the subsequent loss of minor satellite sequences are possible through processes such as unequal crossing over or looping out unstable inverted minor satellite sequences generated from the translocation events (25,(28)(29)(30). Rob translocations constitute the most common chromosomal rearrangement observed in humans.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, several patterns of rep DNA-karyotype changes have been described, and practically all the possible combination of changes, and non-changes, of the two parame ters have been found, totally confusing our view of the phenom enon, one finding the example that better fits his own view of genome restructuring during evolution (Hatch et al, 1976, in the kangaroo rats of the genus Dipodomys; Patton and Sher wood, 1983, in the pocket gophers of the talpoides and hottae species group of the genus Thomomys; Garagna et al [1993Garagna et al [ , 1995, in 2n differently set up house mouse Mus domestieus wild populations). Thus, apparently it is not possible to formu late a unifying theory accounting for the role played by rep DNA in karyotype restructuring.…”
Section: Discussionmentioning
confidence: 99%